2019
DOI: 10.3390/agriculture9020029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Manure Application and Prolonging Mid-Season Drainage on Greenhouse Gas Emission from Paddy Fields in Ehime, Southwestern Japan

Abstract: Green manure application helps maintain soil fertility, reduce chemical fertilizer use, and carbon sequestration in the soil. Nevertheless, the application of organic matter in paddy fields induces CH4 and N2O emissions. Prolonging mid-season drainage reduces CH4 emissions in paddy fields. Therefore, the combined effects of green manure application and mid-season drainage prolongation on net greenhouse gas emission (NGHGE) were investigated. Four experimental treatments were set up over a 2-year period: conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…These studies also indicate that the effects of straw addition on CH 4 emissions are sturdily dependent on management (water management that promotes aerobic conditions during drainage) and climatic conditions, as reported in our previous study [34]. It can also be attributed, however, to the delay in reducing N 2 O to N 2 by denitrification [57].…”
Section: Greenhouse Gas Fluxes (R M Ch 4 and N 2 O)supporting
confidence: 75%
See 1 more Smart Citation
“…These studies also indicate that the effects of straw addition on CH 4 emissions are sturdily dependent on management (water management that promotes aerobic conditions during drainage) and climatic conditions, as reported in our previous study [34]. It can also be attributed, however, to the delay in reducing N 2 O to N 2 by denitrification [57].…”
Section: Greenhouse Gas Fluxes (R M Ch 4 and N 2 O)supporting
confidence: 75%
“…In this study, total N 2 O emissions were higher in the fallow season than in the rice growing season, possibly due to the comparatively low rate of N fertilization, rice straw, and water management. Nishimura et al [56] and Toma et al [57] have reported similar findings. During the rice growing season, we observed very low N 2 O emissions, although these fields received enormous amounts of rice straw and different water management.…”
Section: Greenhouse Gas Fluxes (R M Ch 4 and N 2 O)supporting
confidence: 53%
“…This study is supported by the findings of Sampanpanish, 28 who reported that the highest application rate of cow dung manure (12.5 t ha −1 ) in rice production in Thailand resulted in the highest rate of methane emissions (4.94 mg m −2 day −1 ) because CH 4 is produced by transforming carbon from organic substrate decomposition into methane. Toma et al 29 . reported higher CH 4 emission (120 mg C m −2 h −1 ) from a higher application rate of plant biomass carbon (green manure at 40 kg ha −1 , weeds and belowground biomass) in paddy fields in southwestern Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In these calculations, the GWP values for CH 4 and N 2 O were considered to be 34 and 298, respectively, ( IPCC, 2013 ). The GWP and soil C sequestration calculations were as below ( Toma et al., 2019 ): GWP CH 4 to CO 2eq = CH 4 –C emission × 16/12 × 34 GWP N 2O to CO 2eq = N 2 O–N emission × 44/28 × 298 where C tre is the soil C content in each treatment after rice cultivation (g kg −1 dry soil), C bef is the soil C content before the experiment (14.50 g kg −1 dry soil), S dw is the amount of soil in the pot at the start of the experiment (4.9 kg dry weight), P area is the pot area (m −2 ), multiplied by a ratio of molecular weight of CO 2 to C (44/12) to calculate C sequestration in CO 2 equivalent. The ratios of 16/12 and 44/28 were used to convert CH 4 –C to CH 4 and N 2 O–N to N 2 O, respectively.…”
Section: Methodsmentioning
confidence: 99%